Açaí (Euterpe oleracea Mart.) Attenuates Oxidative Stress and Alveolar Bone Damage in Experimental Periodontitis in Rats - Vinicius Ruan Neves dos Santos; Deborah Ribeiro Frazão; Railson de Oliveira Ferreira; Paulo Fernando Santos Mendes; Daiane Claydes Baia-; Deiweson Souza-Monteiro; Leonardo Oliveira Bittencourt; João Daniel Mendonça de Moura; José Messias Perdigão; Bruno José Brito Teixeira; Everton Luiz Pompeu Varela; Gabriela de Souza Balbinot; et al. (MDPI AG, 2022)
Açaí (Euterpe oleracea Mart.) juice is rich in phenolic compounds with high antioxidant capacity. It has been observed that the use of antioxidants may be an additional strategy to nonsurgical periodontal therapy as well as to prevent alveolar bone loss. Thus, the objective of this study was to investigate the effects of açaí supplementation on experimental periodontitis in rats. Twenty male Rattus norvegicus (Wistar) rats were assigned into control, açaí, experimental periodontitis, and experimental periodontitis with açaí supplementation groups. Periodontitis was induced by placing ligatures around the lower first molars. Animals in the açaí groups received 0.01 mL/g of clarified açaí juice for 14 days by intragastric gavage. At the end of the experimental period, blood was collected to assess the reduced glutathione (GSH), Trolox equivalent antioxidant capacity (TEAC), and lipid peroxidation (TBARS) levels. Moreover, hemimandibles were analyzed by micro-computed tomography (micro-CT) for alveolar bone loss and bone quality. Açaí supplementation increased blood total antioxidant capacity and decreased lipid peroxidation. It also reduced alveolar bone loss when compared to the experimental periodontitis group. Moreover, clarified açaí per se modulated the oxidative biochemistry and bone microstructure. Thus, açaí may be considered a viable alternative for managing periodontal oxidative stress and preventing alveolar bone loss.